2021
DOI: 10.1016/j.jhep.2021.01.032
|View full text |Cite
|
Sign up to set email alerts
|

EASL position paper on the use of COVID-19 vaccines in patients with chronic liver diseases, hepatobiliary cancer and liver transplant recipients

Abstract: According to a recent World Health Organization estimate, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, which originated in China in 2019, has spread globally, infecting nearly 100 million people worldwide by January 2021. Patients with chronic liver diseases (CLD), particularly cirrhosis, hepatobiliary malignancies, candidates for liver transplantation, and immunosuppressed individuals after liver transplantation appear to be at increased risk of infections in general, which in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
215
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(240 citation statements)
references
References 60 publications
4
215
0
10
Order By: Relevance
“…The second study from Tel-Aviv Sourasky Medical Center, Israel, evaluated humoral antibody responses in 80 LTR and 25 healthy volunteers after vaccination with the mRNA vaccine BNT162b2 (BioNTech/Pfizer). The study confirmed the concern of lower immunogenicity of vaccination in transplant recipients (reviewed in [1]); antibodies were detectable in only 47.5% of patients compared to all 25 healthy controls and antibody titers were significantly lower in LTR (95.41 AU/mL vs. 200.5 AU/mL, p<0.001) [3]. Importantly, the authors reported no serious adverse events associated with the vaccine, and no event of graft rejection was observed.…”
Section: Editorialsupporting
confidence: 71%
See 3 more Smart Citations
“…The second study from Tel-Aviv Sourasky Medical Center, Israel, evaluated humoral antibody responses in 80 LTR and 25 healthy volunteers after vaccination with the mRNA vaccine BNT162b2 (BioNTech/Pfizer). The study confirmed the concern of lower immunogenicity of vaccination in transplant recipients (reviewed in [1]); antibodies were detectable in only 47.5% of patients compared to all 25 healthy controls and antibody titers were significantly lower in LTR (95.41 AU/mL vs. 200.5 AU/mL, p<0.001) [3]. Importantly, the authors reported no serious adverse events associated with the vaccine, and no event of graft rejection was observed.…”
Section: Editorialsupporting
confidence: 71%
“…Reported patients were rather young (median age 39 years) and only 3.7% had diabetes mellitus, a main risk factor for steatohepatitis and disease progression. This suggests that study participants had no advanced CLD and might explain why these findings are different to what is seen with other vaccines, such as influenza, where patients with advanced CLD elicit lower humoral immune responses [1]. More data on COVID-19 vaccination in patients with advanced CLD and with different vaccine types are eagerly awaited.…”
Section: Editorialmentioning
confidence: 95%
See 2 more Smart Citations
“…Coronavirus disease 2019 (COVID-19) has caused a devastating global pandemic since early 2020. 1 , 2 We read with interest the recent article by Cornberg et al. , 1 in which they summarized the data on vaccine safety, immunogenicity, and efficacy in patients with chronic liver diseases, hepatobiliary cancer and liver transplant recipients.…”
Section: Introductionmentioning
confidence: 99%